Do players in Spanish professional soccer leagues maintain match running performance until the end of the match? A 5-minute interval analysis by match participation - García-Calvo, T.; Lobo-Triviño, D.; Ponce-Bordón, J. C.; Sanabria-Pino, B.; López del Campo, R.; Resta, R.; Chmura, P. (Biology of Sport, 2025)
The present study aimed to analyse the match running performance differences across 5-minute time intervals considering the players` participation in matches. A total of 381,194 individual match observations from professional soccer players competing in the First (n = 171,957) and Second (n = 209,237) Spanish soccer leagues over the 2022/23 season were collected. Soccer players were classified according to their participation in matches. Total distance (TD), very high-speed running (VHSR, 21-24 km × h-1), and sprinting speed running distance (Sprint, > 24 km × h-1) were analysed using a computerized tracking system (TRACAB, Chyronhego, New York, NY). Match data were divided into pre-defined 5-minute intervals. Linear mixed models were performed to analyse match running performance over the 5-minute intervals while controlling the influence of match participation. The main results showed a decrease in match running performance as the match time progressed, from the 55th-60th minute onward (p < .001), although match participation also had a significant influence. Specifically, substitute players covered significantly greater VHSR (p < .001) and Sprint distances (p < .001) than the rest of the players during their time of participation. These findings provide knowledge about the evolution of match running performance over match time. Finally, analysis of 5-minute intervals may help coaches understand the periods of matches where player substitutions are most effective.